KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI - Sari, Lisa Purnama; Asri, Yasnur; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this study was to describe the correlation vocabulary with exposition text writing skills of students of class VII SMP Negeri 8 Padang. This research data is the result of the test writing skills scores exposition text using descriptive methods. Data were collected through performance tests. The results of this study is the correlation vocabulary with exposition text writing skills of students of class VII SMP Negeri 8 Padang at significant level of 95% with degrees of freedom (n-1), were tvalue >ttable (2.89> 1.67). Ho was rejected and H1 was accepted because the results of the hypothesis test prove that value of tvalue was bigger than ttable.Â Kata kunci: korelasi, kosakata, keterampilan, menulis teks eksposisi